PENTINGNYA PENGUASAAN LITERASI TEKNOLOGI INFORMASI DAN KOMUNIKASI BAGI GURU MADRASAH IBTIDAIYAH DALAM MENYIAPKAN SISWA MENGHADAPI REVOLUSI INDUSTRY 4.0 - Munawir Gazali; Made Ayu Pransisca (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
In the era of the industrial revolution 4.0, it is a tough challenge for all Indonesian teachers. The quality of education is a measure of Indonesia's success in facing the era of the industrial revolution 4.0. A teacher at this time is required to be technologically literate because the quality of a teacher who is empty of technology will not be able to instill a "critical character" in students to become revolutionary humans. This study discusses the development of mastery of information and communication technology literacy at Madrasah Ibtidaiyah. Information and Communication Technology literacy includes the ability to use technology as a tool to research, organize, evaluate and communicate information, and have a fundamental understanding of ethical legal issues surrounding the access and use of information. There are seven elements of Information and Communication Technology literacy, namely: define, access, evaluate, manage, integrate, create, and communicate. Developing a learning framework in the 21st century that requires students to have skills, knowledge and abilities in the fields of technology, media and information, learning and innovation skills as well as life and career skills. The types of sources and learning media based on Information and Communication Technology that can be utilized by elementary school teachers in the learning process include: (1). Computer (2). LCD (3). Internet (4). Learning CD, (5) email (6). Power Point Presentation (7) Multimedia. In the learning process, using media is very important to increase interest and understanding of materials such as Augmented Reality-based learning media. Become a technology literate teacher and really need support from the government. Information and Communication Technology literacy can be done by participating in socialization, training, upgrading, seminars and workshops on Information and Communication Technology